Introducing Windows Azure - Li, Henry (Apress : Imprint: Apress, 2009)
Windows Azure is Microsoft's next-generation cloud-computing operating system and is designed to provide companies with new business opportunities as they migrate toward hosted services. Introducing Microsoft Azure provides all the information developers need to get started with this technology and apply it across a range of situations. Presented in a clear, concise manner, this book provides a carefully measured learning curve for surmounting the architectural and coding challenges that need to be faced when building a well-balanced Windows Azure service.